Bending Behavior of Composited Rubber-Wood Beam Reinforced with Fiber Rods - Chuchaycom, Apisit; husilp, Nuntachai; Anusiri, Manat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
Wood is one of the most popular and widely accepted materials for both load-bearing and load-bearing structures. The direct use of rubber wood as a load-bearing structure might not be employed hence reinforcement with fiber is a way to improve the structure. However, the use of fiber materials is still limited. Insufficient relevant research was found to assess the behavior and load carrying capacity of structures. Therefore, this study aimed to present an assessment of the behavior and load carrying capacity of structures. Bending properties of beams with fiber reinforcement patterns in different positions with stress analysis at rupture point stress interactions were presented. Maximum elastic modulus and shear unit were used in estimating the maximum bending moment strength. The results of the tests were analyzed leading to an understanding of the behavior as well as further assessment of the loading efficiency.